Development of an Integrated Halal Tourism Website to Strengthen Tourism Stakeholders in Labuan Bajo - Sari, Puspa Novita; Suprapti, Suprapti; Udin, Bagus Sholeh (Institut Teknologi Nasional, Bandung, 2026)
The Community Service Program aims to empower tourism actors in Labuan Bajo through the development of an integrated halal tourism website to enhance digital visibility and support Muslim-friendly tourism. Despite its status as a super-priority destination, many tourism stakeholders face limitations in digital utilization. A total of 35 tourism actors participated in training on halal tourism literacy, Google Business Profile optimization, and website management. The developed platform integrates business profiles, mosque locations, tourist destinations, and initial MSME e-commerce features. The results indicate an 18.41% increase in participants’ digital literacy scores, with 100% participants successfully integrated into Google Business Profile and the website platform. High participant satisfaction (94,33%) further reflects the effectiveness of the program. Overall, the program strengthens the digital capacity of local tourism actors and enhances the visibility of halal tourism in Labuan Bajo. Continuous content development and ongoing website optimization are recommended to ensure sustainability and long-term impact.